Effect of Functional Task Exercise Program on Functional Activity, Balance and Quality of Life in Elderly Population. - Mitali S Purandare; Dr. Shweta Kulkarni; Dr. Tushar Dhawale (International Journal of Allied Medical Sciences and Clinical Research, 2021)
BackgroundElderly group of people are defined as the individuals of 65 years or above. Changes in neuromuscular and musculoskeletal system of an individual’s causes restriction in his balance and functional activities because of normal aging process. Hence it is important to study the balance, functional activity and also quality of life. An important strategy for the Reduction or prevention of functional decline during ageing is - regular physical activity and generally physical activity reduces the risk of disease and has a beneficial effect on the impact of a large number of chronic diseases therefore increasing physical activity in elderly is relevant and very important to maintain quality of life.(15) Functional Task Exercises can achieve enduring effects because it enhances older people physical capacity, improves motor performance and also because it fits in with daily routine. MethodsEthical clearance was taken from institutional ethical committee.The aims and objectives of research were explained and willing participants were included in the study after the written consent was obtained. ResultsA total of 30 elderly people were included. Functional activity measured by FIM Scale before and after the intervention in both the Groups were improved, but more in Group A (FTE) compared to Group B (conventional exercises). Group A showed mean of (104.66 + 3.457) before and (108.46 + 4.068) after the intervention whereas Group B showed the mean of (103.33 + 3.331) before and (105.4 + 3.312) after the intervention. Balance which is measured by POMA scale is improved in both the Groups A and B but more in Group A (FTE). 4Before intervention the mean of Group A was (13.13 + 1.245) and after was (14.8 + 1.060). Group B had a mean of (12.8 + 1.146) before and (13.73 + 1.163) after intervention. Quality of life was improved more in Group A as compared to Group B with p<0.0001 which is extremely significant as the level was set as p<0.05. Group A showed mean of (123.33 + 4.73) before and (152.27 + 5.57) after the intervention and Group B showed mean of (125.06 + 5.93) before and (143.20 + 3.95) after the intervention. Conclusion: The study concludes that functional task exercise program along with conventional exercises showed more improvement in elderly than conventional exercises.